2019
DOI: 10.1177/0300060519862055
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting retrieval of 12 or more lymph nodes in pT1 colorectal cancers

Abstract: ObjectiveThe aim of this study was to identify clinicopathological factors that affect the number of lymph nodes (LNs) (12 or more) retrieved from patients with colorectal cancer (CRC), particularly those with pathologic T1 (pT1) disease.MethodsFrom 429 CRC patients, 75 pT1 cancers were identified and digitally scanned. Binary logistic regression analysis was performed to identify the clinicopathological factors affecting the number of LNs retrieved from all 429 patients and from the subset of patients with pT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Further, this strong immune response against the tumour will result in improved patient survival, as has been shown in many clinical studies [ 17 , 18 , 33 ]. The effect of local immune response on nodal hyperplasia resulting in enlarged lymph nodes has been studied previously [ 34 ]. We are not the first to find an association between immune response in the primary tumour and LN yield, however, the two previous studies we cite showed only weak associations and only in T cells [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, this strong immune response against the tumour will result in improved patient survival, as has been shown in many clinical studies [ 17 , 18 , 33 ]. The effect of local immune response on nodal hyperplasia resulting in enlarged lymph nodes has been studied previously [ 34 ]. We are not the first to find an association between immune response in the primary tumour and LN yield, however, the two previous studies we cite showed only weak associations and only in T cells [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding T1 CRC, Bakes et al reported that a lymph node yield of <10 was associated with an increased risk of recurrence after surgical resection [50]. In addition, the number of lymph nodes retrieved in leftsided disease including the rectum was less than in rightsided [50,51]. This difference may be because right-sided CRC resection specimens were longer than left-sided CRCs, or there was variable lymphatic anatomy between them [52].…”
Section: Recurrencementioning
confidence: 99%
“…Finally, 54 studies were included, with 30 included in the systematic review,5 19–47 and 24 in the meta-analysis (figure 1). 12–14 48–68…”
Section: Resultsmentioning
confidence: 99%